PERAN AKTIF CIVITAS AKADEMI MARITIM NUSANTARA BANJARMASIN DALAMRANGKA PERINGATAN MAULID NABI MUHAMMAD SAW - Andri Ali Wardhana; David Bastian Sihombing; Edision; Etik Purewati; Susi Herawati (Akademi Maritim Nusantara Banjarmasin, 2022)
AbstractThe role is defined as a device of behavior that is expected to be possessed by people who aredomiciled in society. Muslim communities in Indonesia generally welcome the Prophet's birthday by holdingreligious celebrations, such as: reciting the Prophet's blessings, reciting Barzanji poetry and reciting recitations.According to the Javanese calendar, the month of Rabiul Awal is called the month of Mulud, and the Muludanevent is also celebrated with celebrations and games of the Sekaten gamelan. Most Sunni and Shiite Muslimcommunities in the world celebrate the Prophet's Birthday. Sunni Muslims celebrate it on the 12th of RabiulAwal while Shia Muslims celebrate it on the 17th of Rabiul Awal, which also coincides with the sixth birthdayof the Shia Imam, namely Imam Ja'far ash-SadiqThis implementation method is in the form of field activities, namely by carrying the theme ofParticipation of the Banjarmasin Nusantara Maritime Academy Cadets in the Active Role of the BanjarmasinNusantara Maritime Academy in the Commemoration of the Prophet Muhammad SAW's Birthday. Thesocialization method is carried out in two main parts, namely presentation of material and questions andanswers about activities the talk.The results of the discussion of the Banjarmasin Archipelago Maritime Academy carry out theseactivities to foster public interest and interest in Islam and the presence of a military-minded sailing school, aschool that produces generations of Islamic-minded people, so that the Banjarmasin people's view knows that inthe military environment it is not rigid from the view of the common people . Apart from that, it proves that asense of tolerance between religious communities is shown in similar activities, it is proven that even in thatenvironment there are cadets who are non-Muslims who also help in religious mattersKeywords. role, active, birthday of the prophet saw.